Finance and Financial Markets / Second Edition - Pilbeam Keith (Palgrave Macmillan, 2005)
A comprehensive and accessible introduction to finance. Preface, The World of Finance, Financial Intermediation and Financial Markets, Financial Institutions, Monetary Policy and Interest Rate Determination, Domestic and International Money Markets, The Domestic and International Bond Market, Portfolio Analysis: Risk and Return in Financial Markets, The Capital Asset Pricing Model, Stock markets and Equities, The Efficiency of Financial Markets, The Foreign Exchange Market, Theories of Exchange Rate Determination, Financial Futures, Options, Option Pricing, Swap Markets, Regulation of the Financial Sector, Glossary, References, Further Reading, Index.